Factors Influencing an Individual’s Investment Decisions: An Analysis of Risk Tolerance as a Mediating Variable - Jolin; Johny Budiman (Fakultas Ekonomi dan Bisnis Universitas Islam DR KH EZ Mutaqien, 2026)
This study examines the influence of financial literacy, overconfidence, firm image, and self-control on investment decisions, with risk tolerance included as a mediating variable for financial literacy and overconfidence. Data were collected from 180 respondents using a questionnaire and analyzed through Structural Equation Modelling (SEM). The findings indicate that financial literacy, overconfidence, and self-control have a positive impact on individual investment decisions. In contrast, firm image and risk tolerance show a positive but insignificant effect. Furthermore, risk tolerance does not mediate the relationship between financial literacy and overconfidence on investment decisions. These results can help investors better understand their capabilities and personality traits when making financial decisions. Additionally, the study highlights the importance for policymakers and financial educators to improve financial literacy and address behavioral aspects influencing investment behavior. Enhancing both knowledge and mindset is essential for empowering individuals to make more informed and rational investment choices.